VILLAGE FUND MANAGEMENT (VILLAGE CASE STUDY IN TANJUNG JABUNG TIMUR REGENCY) - Suryani, Arna (Dinasti Publisher, 2021)
This study aims to determine the process of planning, implementation, administration, reporting, and accountability for using village funds in several villages in the Tanjung Jabung Timur Regency Government. The object of this research is the realization of villages in East Tanjung Jabung Regency where the absorption of village funds is less than 50%. The study used qualitative methods using the Nvivo 12 plus analysis tool. The data in this study were obtained through interviews and supported by documents as data. The selection of sources is made by the purposive sampling method. The results showed that the planning process involved the village community in formulating village development plans. The process of implementing and administering development, rehabilitation, and maintenance of infrastructure is carried out in a self-managed manner under SKB Number 49 of 2015 using resources, local raw materials, and labor from the local village community. The reporting and accountability process has been carried out by making reports in several stages and reports on the realization of the use of village funds. As a form of transparency, an information board was created to contain the village's funds, funding sources, and activity plans. There are still several obstacles to the non-absorption of village funds caused by the Village Fund, including the lack of human resource capabilities at the village level in terms of managing and reporting self-management work. In addition, there are natural factors that hinder, such as rainfall and demanding access to work locations. Acquired workshops for village assistants whom the government trains to assist the implementation of village fund management.